2013
DOI: 10.1177/0146167212472541
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Get Your Hopes Up

Abstract: We examine whether lower expectations for social reward selectively applied to high intimacy contexts may help avoidantly attached individuals minimize distress from reward loss. Studies 1, 2, and 4 demonstrated that avoidant attachment was negatively associated with perceived intimacy potential in relationships involving approach of closeness (current/future partners), but not for relationships less associated with approach of closeness (ex-partners). Studies 3 and 5 manipulated the potential for intimacy amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 35 publications
3
30
1
2
Order By: Relevance
“…Overall, then, we suggest that to best understand the factors that influence commitment in romantic relationships, social threat and reward need to be directly accounted for as having independent influences on commitment processes. Although commitment has not been studied in this context, the few studies that have examined the influence of social threat and reward simultaneously on relationship outcomes provide support for the notion that reward is a significant motivator in relationships over and above threat (Lewandowski & Ackerman, 2006;Spielmann et al, 2012;Spielmann, Maxwell, MacDonald, & Baratta, 2013). For example, Lewandowski and Ackerman (2006) showed that a perceived lack of opportunities for self-expansion was a risk factor for infidelity over and above feelings of security.…”
Section: Considering Both Rewards and Threats In Commitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, then, we suggest that to best understand the factors that influence commitment in romantic relationships, social threat and reward need to be directly accounted for as having independent influences on commitment processes. Although commitment has not been studied in this context, the few studies that have examined the influence of social threat and reward simultaneously on relationship outcomes provide support for the notion that reward is a significant motivator in relationships over and above threat (Lewandowski & Ackerman, 2006;Spielmann et al, 2012;Spielmann, Maxwell, MacDonald, & Baratta, 2013). For example, Lewandowski and Ackerman (2006) showed that a perceived lack of opportunities for self-expansion was a risk factor for infidelity over and above feelings of security.…”
Section: Considering Both Rewards and Threats In Commitmentmentioning
confidence: 99%
“…Individuals who are relatively high on the dimension of attachment anxiety experience chronic activation of the attachment system, thus motivating chronic pursuit of reassurance (Mikulincer & Shaver, 2007). They have been shown to appraise ambiguous information as threatening and tend to exaggerate the meaning and importance of potentially threatening behaviors from their partner (Alexander, Feeney, Hohaus, & Noller, 2001;Cassidy & Kobak, 1988;Spielmann, Maxwell, et al, 2013). They are also quick to detect any sign of potential social threat (Ein-Dor, Mikulincer, & Shaver, 2011).…”
Section: Attachment Styles and Perceptions Of Reward And Threatmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the interdependent nature of intimate relationships, there are a myriad of instances when people may perceive threats to their relationships-each of which may fluctuate from day-to-day. Past research has conceptualized the experience of relationship threats in a number of ways, including: perceived regard (Cavallo, Fitzsimons, & Holmes, 2009;Derrick, Leonard, & Homish, 2012;Overall & Sibley, 2009), perceived rejection (Downey, Freitas, Michaelis, & Khouri, 1998;Norona & Welsh, 2016), perceived threats of negative evaluation (Spielmann, MacDonald, & Tackett, 2012;Spielmann, Maxwell, MacDonald, & Baratta, 2012), responsiveness to needs (Feeney & Lemay, 2012;Kane et al, 2007;Laurenceau, Barrett, & Rovine, 2005;Reis, 2014), and perceived availability of support (Fivecoat, Tomlinson, Aron, & Caprariello, 2015;Kane et al, 2007). It is important to understand how state-based relationship threats are innately related as they may cause feelings of doubt and uncertainty about one's relationship, which can be experienced at any time (and may never truly disappear), and also have the potential to cause detrimental experiences within the relationship (Baxter & Montgomery, 1996;Honeycutt, 1993;Planalp & Honeycutt, 1985;Planalp, Rutherford, & Honeycutt, 1988).…”
Section: State-based Relationship Threatsmentioning
confidence: 99%
“…Similarly, avoidant individuals are more likely to make sacrifices (i.e., a pro-relational behaviour) for avoidant motives (i.e., to avoid negative outcomes) than they are to make sacrifices for approach motives (i.e., to add positive outcomes; Mattingly & Clark, 2012). People with avoidant attachment styles also tend to have low hopes for the future in order to circumvent the activation of the attachment system (Spielmann, Maxwell, MacDonald, & Baratta, 2012). In particular, when people with higher attachment avoidance perceive greater potential for intimacy in their relationships and they set lower expectations for connection (i.e., a social reward).…”
Section: Trait-based Threats and Relational Self-expansionmentioning
confidence: 99%